Isolation of a Polyvalent Bacteriophage for Escherichia coli, Klebsiella pneumoniae, and Aerobacter aerogenes - Souza, K. A. (1972)
A lytic bacteriophage isolated from sewage was found to attack strains of Aerobacter aerogenes, Escherichia coli, and Klebsiella pneumoniae, but not members of the genera Salmonella, Proteus, and Serratia. The phage, designated φmp, contained deoxyribonucleic acid with a 50% guanine plus cytosine ratio and a molecular weight of 23.1 × 10(6) daltons. Single-step growth experiments of φmp plated at 37 C on A. aerogenes A2 gave a mean latent period of 20 min, an average burst size of 103 plaque-forming units/infected cell, and an average adsorption rate constant of 3 × 10(−10) ml/min. Electron microscopy of φmp revealed a phage with a flexible tail (165 nm long and 6 nm wide). The phage head had a hexagonal outline (62 nm in diameter).